UZBEK CLASSICAL MUSIC: HISTORY AND DEVELOPMENT OF MAKOM (TAMADDUN NURI JURNALI, 2025)
This article explores the history of the formation and development of Uzbek classical music, with a particular focus on one of its most significant genres - the maqom. The origins of the maqom tradition, its theoretical foundations, and its role in the spiritual and cultural life of the peoples of Central Asia are examined. Special attention is given to the Uzbek school of maqom performance, its unique characteristics, and the contributions of renowned masters and composers in preserving and developing this musical heritage.